User clustering and resource allocation in downlink CoMP with NOMA - Norshidah Katiran; Shaharil Mohd Shah; Noorsaliza Abdullah; Aimi Syamimi Abdul Ghaffar; Faiz Asraf Saparudin (Institute of Advanced Engineering and Science, 2019)
In coordinated multipoint (CoMP) system, the cell-edge performance is improved by minimizing inter-cell interference (ICI) through coordination of resources. Additionally, the non-orthogonal multiple access (NOMA) has been introduced as a promising candidate to further enhance the throughput of next generation wireless communication systems. NOMA allows multiple users to access the wireless channel in the same bandwidth simultaneously, however at different transmit power. In joint transmission NOMA in CoMP (JT-NOMA-CoMP), multiple cells jointly transmit data to users using the same time-frequency resources, which significantly improves the system performance. In this paper, we present a low-complexity user clustering and resource allocation strategy in downlink JP-NOMA-CoMP system with multiple antenna. Based on computer simulation, we show that the proposed approach outperforms the conventional JP-OMA-CoMP and single antenna JP-NOMA-CoMP in terms of achievable sum rate.